PENGARUH SERVANT LEADERSHIP DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI SELF EFFICACY - Yulyanti Fahruna (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Good performance is optimal, efficient and effective performance, namely performance that is in accordance with organizational standards and supports the achievement of organizational goals. Employee performance is influenced by several factors including Servant Leadership and Organizational Climate and is influenced by Self Efficacy. Servant Leadership is an attitude and behavior of a leader who prioritizes the development and interests of subordinates, without thinking about personal gain, Organizational Climate is something that was created to influence employees to obtain good performance, through the internal environment so as to create work motivation, and Self Efficacy is an individual's assessment of his ability or competence to perform a task, achieve a goal, and produce something. This study aims to examine and analyze the influence of Servant Leadership and Organizational Climate and is influenced by Self Efficacy on employee performance in three sub-district offices of Kapuas Hulu district. The population in this study were all employees at the Pontianak City Inspectorate, West Kalimantan Province. The sample in this study were 71 respondents. The data analysis model used is Path Analysis. Based on the results of the study, it shows that Servant Leadership and Organizational Climate and is influenced by Self Efficacy can predict or explain its effect on employee performance. The results of the t-test of Servant Leadership and Organizational Climate and influenced by Self Efficacy have a significant effect on employee performance.